Synergistic Antidepressant Effect of Ginkgo biloba and Withania somnifera Using Experimental Animals - Bairagi, Vinod Ashokdas; Kharnare, Rutika Mahendra; Nikam, Kajal Satish; Ahire, Yogesh Suresh (International Journal of Pharmaceutical Investigation, 2025)
Aim This study involved the antidepressant activity of Ginkgo biloba and Withania somnifera in mice. Depressive disorder is a prevalent psychiatric Condition, affecting 21% of the global population. The currently used drugs can impose a variety of side-effects including cardiac toxicity, hypotension, sexual dysfunction, weight gain and sleep disturbances. In the last decade, there has been growing interest in the therapeutic effects of natural products on mental disorders. Ginkgo biloba and Withania somnifera were investigated for their antidepressant activity. Materials and Methods Antidepressant activity was investigated by using Open Field Test (OFT) and Tail Suspension Test (TST) models. Imipramine was used as reference standards. Results and Conclusion Our study observed that both the Ginkgo biloba and Withania somnifera significantly reduced immobility in the tail suspension test and the open field test model of depression, comparable to Imipramine. However, further studies are needed to understand the mechanism of action and identify the active components responsible for the antidepressant-like activity.
Keywords: Ginkgo biloba; Withania somnifera; Imipramine, Antidepressant